2005
DOI: 10.1103/physrevlett.94.247402
|View full text |Cite
|
Sign up to set email alerts
|

Negative Refraction and Imaging Using 12-fold-Symmetry Quasicrystals

Abstract: Recently, negative refraction of electromagnetic waves in photonic crystals was demonstrated experimentally and subwavelength images were observed. However, these investigations all focused on the periodic structure. Here, we report a new theoretical and experimental finding that negative refraction can appear in some transparent quasicrystalline photonic structures. The photonic quasicrystals (PQCs) exhibit an effective refractive index close to ÿ1 in a certain frequency window. The index shows small spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
65
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 39 publications
8
65
1
Order By: Relevance
“…Nonetheless, PQC can still have relatively sharp diffraction patterns due to longrange order. Such patterns confirm the existence of wave scattering and interference, providing similar functionalities as periodic counterparts, such as photonic band gaps [12][13][14][15], negative refraction [16], lasing [17][18][19], and nonlinear light propagations [20][21][22]. We will show theoretically and experimentally that some two-dimensional photonic quasicrystalline approximants can possess conical dispersion at k ¼ 0, and their finite-sized counterparts can behave like a zero-refractive-index medium as evidenced by different experimental measurements.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Nonetheless, PQC can still have relatively sharp diffraction patterns due to longrange order. Such patterns confirm the existence of wave scattering and interference, providing similar functionalities as periodic counterparts, such as photonic band gaps [12][13][14][15], negative refraction [16], lasing [17][18][19], and nonlinear light propagations [20][21][22]. We will show theoretically and experimentally that some two-dimensional photonic quasicrystalline approximants can possess conical dispersion at k ¼ 0, and their finite-sized counterparts can behave like a zero-refractive-index medium as evidenced by different experimental measurements.…”
supporting
confidence: 52%
“…Photonic quasicrystal (PQC) is constructed by building blocks positioned on well-designed patterns but lacks translational symmetry [12][13][14][15][16][17][18][19][20][21][22][23]. Nonetheless, PQC can still have relatively sharp diffraction patterns due to longrange order.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The super-prism effect is another exciting property arising from the photonic crystals [19,32]. Extensive numerical [21,33,34] and experimental studies [35][36][37] provided a better understanding of negative refraction, focusing and sub-wavelength imaging in photonic crystal structures. Masaya Notomi showed that refraction-like behaviour could be expected to occur in photonic crystals that exhibit negative refraction for certain lattice parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated theoretically and experimentally that both left-handed metamaterials [4 -7] and photonic crystals [8][9][10][11][12][13][14][15] can achieve NR from microwave to near-infrared frequencies. Furthermore, all-angle NR (AANR) for lens imaging at microwave frequencies by metamaterials [16,17] and at optical frequencies by photonic crystals [18,19] has also been demonstrated recently, but the operating bandwidth is still limited in a narrower frequency range [16 -19], and the realization of broadband AANR at an optical frequency, especially in the visible region, is still a challenge.Generally speaking, a periodic structure is capable of producing NR for electromagnetic waves. For example, a simple dielectric waveguide array can bend light in the direction opposite to that observed in common media at a limited incident angle within a narrow frequency bandwidth [20,21].…”
mentioning
confidence: 99%